The Sign of Unity and the Bond of Charity: On the Eucharist as a “Taskmaster” in the Context of Global Migration - Suna-Koro, Kristine (Dialog, 2014)
What does the Eucharist—seen as the source and summit of Christian life and the “meeting-point on which all the issues of theology converge” (Y.Brilioth) have to do with migrants and refugees? Regardless of how we celebrate the Eucharist, we all have to negotiate ways of living together within the interdependent destiny of globalization. Precisely within this global conviviality, the sacramental and mystical radicalism of unity and love that Martin Luther advocated in his eucharistic theology invites serious consideration but also equally serious contextualization.